RASE gathers in honey experts - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
The RASE Symposium at the Royal Show in 1990 will link with the British Beekeepers' Association and the world association Apimondia to explore the topic 'The Contribution of the Honey Bee to Agriculture and the' Countryside'. The symposium hopes to...